Supporting Growth and Stability in Afghanistan : The Country Partnership Framework Summary 2017 to 2020 - World Bank Group (World Bank, Kabul, 2017)
There have been substantial improvements in development outcomes in Afghanistan since 2001, particularly in terms of improved access to basic services such as water, sanitation, and electricity, and increased human development in education and health. However, some gains are now being eroded due to growing insecurity, stagnating growth, and rising levels of poverty. Economic growth in Afghanistan has slowed after a period of rapid growth between 2003 and 2012. While the Government of Afghanistan is committed to an ambitious reform program, it is doing so in the midst of political and economic uncertainty. Afghanistan remains a deeply fragile and conflict-affected country. The long years of war have hollowed out state institutions and led to widespread disenchantment with the ruling elite and have fueled the Taliban insurgency. Internal displacement as a result of conflict has led to over 1 million internally displaced persons.At the same time, the country’s difficult topography, vulnerability to climate change, and growing population at 3 percent a year have imposed additional constraints on development. For economic growth to have any impact on poverty, it has to be particularly high and broad based to compensate for the high population growth rate and youth bulge. At nearly 50 percent, Afghanistan’s proportion of population aged 15 years or below is the second highest in the world. Poor nutrition, especially of children, threatens welfare and education gains.